MAIMOON PALACE IN THE MIDST OF SOCIAL REVOLUTION: ITS ROLE IN MAINTAINING MALAY IDENTITY IN POST-INDEPENDENCE MEDAN - Rudiansyah Tanjung; Achiriah Achiriah (Journal Analytica Islamica, 2025)
The 1946 Social Revolution in East Sumatra brought major changes to the power structure of the Malay Sultanates, including the Deli Sultanate. Although many palaces were destroyed, Maimun Palace remained as a symbol of glory and Malay cultural identity in Medan. This study aims to describe the condition of Maimun Palace after the social revolution and analyze its role in maintaining Malay identity in the post-independence era. The method used is a qualitative historical approach, with the stages of heuristics, source verification, interpretation, and historiography. Data were obtained through semi-structured interviews, field observations, and archival documentation and supporting literature. The results of the study indicate that Maimun Palace has a strategic role as a center for preserving Malay culture, both through architecture that reflects the acculturation of Malay, Islamic, Indian, and European cultures, as well as through social and tourism activities that strengthen Malay identity in Medan. Despite facing the challenges of urbanization and a lack of government attention, Maimun Palace remains a symbol of cultural permanence and pride of the Malay community amidst the currents of modernization and multiculturalism in Medan.